Limiting factor for developing soybean under tropical climatic conditions in lowland areas of Tanjung Lago Banyuasin District - Fuja Aslamiyah Utami; Momon Sodik Imanudin; Dedik Budianta (Jurnal Lahan Suboptimal : Journal of Suboptimal Lands, 2025)
Tidal lowlands have a wide distribution in Indonesia and have the potential to support the development of soybean cultivation. However, soybean cultivation in the tidal lowlands often faces various challenges. The study aimed to identify land suitability, limiting factors, and soybean cultivation strategies in tidal lowland type B. This study used a survey method, and sampling points were determined by the purposive sampling method. The research was carried out in several stages, namely preparation, field activities, laboratory analysis, and data analysis. Data analysis was carried out by matching the results of field and laboratory analysis with the requirements for soybean land suitability. The results of the study showed that the research land was moderately suitable for soybean cultivation in terms of the actual land suitability level, namely S3-wa, nr, na, and xs with limiting factors of rainfall, soil pH, C-Organic, K2O, and pyrite depth. While the potential land suitability class could be done by improving irrigation and drainage channels, liming, adding organic matter, fertilization, and regulating the water level with high-level management (++) to potential suitability S1 (very suitable) and for pyrite problems (FeS2) through moderate management (+) with groundwater level control to potential suitability S2 (moderately suitable). Management recommendations that can be applied to soybean cultivation were to regulate planting patterns and micro water management.